2015
DOI: 10.1007/s11605-015-2944-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Marker Expression Is Highly Heterogeneous in Esophageal Adenocarcinoma and Does Not Predict a Response to Neoadjuvant Therapy

Abstract: A reliable method to identify pathologic complete responders (pCR) or non-responders (NR) to neoadjuvant chemoradiation therapy (NAT) would dramatically improve therapy for esophageal cancer. The purpose of this study is to investigate if a distinct profile of prognostic molecular markers can predict pCR after neoadjuvant therapy. Expression of p53, Her-2/neu, Cox-2, Beta-catenin, E-cadherin, MMP-1, NFkB, and TGF-B was measured by immunohistochemistry in pre-treatment biopsy tissue and graded by an experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…But imaging methods such as PET-CT following NCRT for esophageal cancer was also not accurate enough to identify patients with pathological response for clinical application (13). Recently, concerns about molecular markers related to the treatment response have been raised by the clinicians and researchers (14,15). However, the clinical application of the markers is not widely available and their clinical relevance needs to be further validated.…”
Section: Discussionmentioning
confidence: 99%
“…But imaging methods such as PET-CT following NCRT for esophageal cancer was also not accurate enough to identify patients with pathological response for clinical application (13). Recently, concerns about molecular markers related to the treatment response have been raised by the clinicians and researchers (14,15). However, the clinical application of the markers is not widely available and their clinical relevance needs to be further validated.…”
Section: Discussionmentioning
confidence: 99%
“…Kitamura et al showed that p53 was significantly associated with increased sensitivity to nCRT, whereas other studies could not confirm this correlation. [44][45][46] The majority of immunohistochemical studies have been performed in patients with ESCC or mixed population of EAC and ESCC patients, therefore to be interpreted with caution. In addition, in contrast to our study, others scored strong nuclear p53 as aberrant only.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have indicated that TGF-β expression is correlated with tumor size, lymph node metastasis, clinical stage and shorter survival in gastric cancer [16,17] and esophageal cancer [18,19]. However, other studies did not find this correlation [20,21] and a few studies even reported an inverse correlation [22,23], which could indicate tumor-restricting properties of TGF-β.…”
Section: Introductionmentioning
confidence: 99%